Effect of tyoe of solvents on asymmetric polyethersulfone PES) membrane for CO2/H4 separation - Nezille Izzie, Anak Lahu (2010)
This study investigates the influences of solvent on the structure and performances of polyethersulfone asymmetric flat sheet membrane for gas separation. The asymmetric flat sheet membrane were prepared by dry/wet phase inversion process consisting polyethersulfone (PES) as polymer, distillate water as a non-solvent and different solvent type was also added either dimethylformamide (DMF), dimethylacetamide (DMAc) or N-methyl-2-pyrrolidone (NMP). The dope formulated contains 20wt% polymer, 75wt% solvent and 5wt% non-solvent. Asymmetric flat sheet membranes were cast using a conventional casting technique. Methanol were used as the coagulation medium. The membranes are coated with 3wt% of polydimethylsiloxane (PDMS) mixed with 97wt% of n-hexane. The morphological structures of produced membranes were examined using Scanning Electron Microscope (SEM). The SEM images exhibited the best morphological structure was discovered from the membrane produced by using NMP as solvent followed by DMAc and lastly DMF. The Fourier Transform Infrared Spectroscopy (FTIR) analysis also conducted in order to detect the existence of the functional groups in the membrane. The performance of the membrane was examined by conducting the gas permeation test. Pure carbon dioxide (CO2) and pure methane (CH4) were used as the test gases by using feed pressure range from 1 to 3 bar. As predicted by the morphological structure, NMP solvent-membrane showed the best performance compared to DMAc solvent-membrane and DMF solvent-membrane. The selectivity of CO2/CH4 was 1.1358 (at 1 bar), 1.9946 (at 2 bar) and 2.6906 (at 3 bar) for NMP solvent-membrane, 1.0564 (at 1 bar), 1.8974 (at 2 bar) and 1.8958 (at 3 bar) for DMAc solvent-membrane and 0.9141 (at 1 bar), 1.7759 (at 2 bar) and 1.5257 (at 3 bar) for DMF solvent-membrane. Hence, solvent was discovered to affect the morphological structure which will consequently affect the performance of the polyethersulfone asymmetric flat sheet membrane. So, from the study conducted on solvent type, the most suitable solvent to produced high performance polyethersulfone asymmetric flat sheet membrane is NMP.